Logistics information systems impact on exporting organizational performance and customer service perceptions: a review - Staub, Selva; Khoury, Sam; Jenab, Kouroush (Nexo Revista Científica, 2024)
This study investigates the influence of perceived logistics service quality on the organizational performance of export-oriented businesses in the Aegean Region. Employing a cross-sectional design, we gathered data from 252 firms through surveys, focusing on their collaboration, expectations, and preferences with logistics service providers. The collected data underwent comprehensive analysis using various statistical methods through SPSS 22.0 software, including One-Way Analysis of Variance (ANOVA), Correlation Analysis, and Regression Analyses, to assess the relationships between variables. Our research findings reveal significant differences in customers' expectations of logistics services concerning factors such as operational information sharing, on-time delivery, and order processing. However, variables related to logistics information technologies and problem-solving show no significant differences in influencing customers' preferences for logistics companies. Notably, responsiveness emerges as a significant variable affecting customers' preferences. In conclusion, this study underscores the pivotal role of technological applications in enhancing both business performance and customer satisfaction within the logistics sector. These findings contribute to the understanding of how logistics service quality and information technologies intersect to shape organizational outcomes, emphasizing the importance of meeting evolving customer satisfaction criteria in this service-based industry.